PROPOSED BUSINESS STRATEGY FOR A FASHION E-COMMERCE SPECIALIST: A QUALITATIVE CASE STUDY OF ZALORA INDONESIA - Alysia Lunar Adriyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Indonesia is the largest e-commerce market in Southeast Asia, with a Gross Merchandise Value of US56.5 billion in 2024. Fashion is consistently the largest online retail category. The market is dominated by three horizontal marketplaces, Shopee, Tokopedia, and TikTok Shop, which together control approximately eighty percent of total transaction value. Within this structure, ZALORA Indonesia operates as a fashion specialist whose parent, Global Fashion Group, reported a 20.3 percent year-on-year decline in Southeast Asia Net Merchandise Value in the fourth quarter of 2024. This study addresses a strategic problem: although ZALORA is widely recognised as a provider of authentic and curated fashion, it captures a disproportionately small share of consumer consideration in a market conditioned by deep promotional subsidies and content-led discovery. The research is guided by two questions: how ZALORA is perceived relative to its competitors on perceived price attractiveness, perceived risk (authenticity assurance), and perceived product assortment; and which business strategy is most suitable for ZALORA Indonesia. The study employs a qualitative descriptive case study design. Primary data were obtained from in-depth, semi-structured interviews with expert informants holding direct experience across ZALORA, TikTok Shop, Tokopedia, and Lazada, in commercial, buying, marketing, and creator-management functions. Interview data were analysed through thematic analysis and mapped onto established strategic frameworks, namely PESTEL, Porter’s Five Forces, competitor analysis, and the VRIO framework, and were triangulated with secondary market data and internal data. The synthesised findings were organised through a SWOT analysis and converted into strategic alternatives using a TOWS matrix. The findings indicate that experts consistently perceive ZALORA as superior on authenticity assurance and luxury assortment, broadly comparable on general assortment, but weaker on perceived price attractiveness because final payable prices on subsidy-heavy platforms are consistently lower. ZALORA’s authenticity guarantee and business-to-consumer sourcing model emerge as a valuable and rare capability, while the absence of a live-commerce feature and centralised, non-localised application development emerge as organisational weaknesses. The study concludes that a focused differentiation strategy, concentrated on curated and luxury fashion, authenticity-led trust, and selective promotional participation, is the most suitable direction for ZALORA Indonesia, and recommends against direct price-led competition with subsidy-driven marketplaces. The contribution of this research is a structured, expert-informed application of strategic frameworks to a specialist e-commerce firm operating within a marketplace-dominated emerging market.